Intervention initiatives to raise young people’s interest and participation in STEM - Schneider, Barbara; Chen, I-Chien; Bradford, Lydia; Bartz, Kayla (Frontiers in Psychology, 2022)
For nearly a decade, two science interventions anchored in project-based learning (PBL) principles have been shown to increase student science learning in elementary 3rd grade and high school physical science classes. Both interventions employed a randomized control trial of several thousand students (N = 3,271 in 3rd grade and N = 4,238 in 10th, 11th, and 12th grades). Incorporating a rich background of research studies and reports, the two interventions are based on the ideas of PBL as well as the National Academies of Science’s publications, including how children learn; how science learning and instruction can be transformed; and the performance expectations for science learning articulated in the Next Generation of Science Standards. Results show significant positive increases in student academic, social, and emotional learning in both elementary and secondary school. These findings can be traced, in part, to carefully crafted experiential participatory activities and high-quality instructional materials which act as strong facilitators for knowledge acquisition and use. Reviewing the innovations undertaken by these two interventions, this article describes the importance of studying social and emotional factors ‘in situ’, using the Experience Sampling Method (ESM), that can motivate and engage students in science learning in both elementary and secondary school. Using these ‘in situ’ data collection (N= 616 students in 3rd and N = 545 students in 10th, 11th, and 12th grades) along with case studies and repeated measures analysis which gave deep insights into emotional and social development for young children and adolescents. These methods should continue to be considered when trying to understand key factors of improving engagement in science.